2005
DOI: 10.1152/japplphysiol.01319.2004
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular size and systolic function in Thoroughbred racehorses and their relationships to race performance

Abstract: Cardiac morphology in human athletes is known to differ, depending on the sports-specific endurance component of their events, whereas anecdotes abound about superlative athletes with large hearts. As the heart determines stroke volume and maximum O2 uptake in mammals, we undertook a study to test the hypothesis that the morphology of the equine heart would differ between trained horses, depending on race type, and that left ventricular size would be greatest in elite performers. Echocardiography was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
2
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 21 publications
7
69
2
9
Order By: Relevance
“…Comparison of echocardiographic measurements in Spanish foals to previously reported values for other equine breeds: LVID, LVFWT, IVST and MV measurements were smaller in the Spanish foals than the values presented for Thoroughbreds [20,31,32] and Standardbreds [1,5,33] older than 20-24 months. In addition to the different age, most of the papers listed above showed data for animals in training.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Comparison of echocardiographic measurements in Spanish foals to previously reported values for other equine breeds: LVID, LVFWT, IVST and MV measurements were smaller in the Spanish foals than the values presented for Thoroughbreds [20,31,32] and Standardbreds [1,5,33] older than 20-24 months. In addition to the different age, most of the papers listed above showed data for animals in training.…”
Section: Discussioncontrasting
confidence: 50%
“…It is tempting to speculate if these (6.295-9.678) data are the result of the genetic selection of Thoroughbred horses for speed racing, whereas the Spanish horses are mainly used for dressage or as saddle horses and genetic selection has followed mainly morphological characteristics. In fact, it has been demonstrated that an eccentric cardiac hypertrophy occurs in response to race training attributable to an increased diastolic stress and thus, higher heart chambers are expected in the trained Thoroughbreds and Standardbreds horses [31][32][33]. Another reason to explain the differences between breeds in the echocardiographic measurements is the effect of HR, which was almost 2-fold higher in the Spanish foals than in Thoroughbreds and Standardbreds [1,5,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Verkürzung der PEP bei Aortenklappeninsuffizienz ist auf die erhöhte Kontraktilität (Ishikawa et al 1975, Lewis et al 1977, Atkins und Snyder 1992 , Stadler et al 1994, Patteson et al 1995, Stadler et al 1995, Young et al 2005, Gehlen et al 2005 Bei den Pferden mit Aortenklappeninsuffizienz (AVI) wurde eine signifikante Erhöhung der systolischen Geschwindigkeiten und der diastolischen Rückflussgeschwindigkeit sowie der Widerstandsindizes und eine verminderte enddiastolische Geschwindigkeit gefunden. Bei AVI ist auch eine erhöhte Vmax an der Aortenklappe zu finden.…”
Section: Materials Und Methodeunclassified
“…Körperliches Training hat eine Auswirkung auf die Herzgröße und die Herzfunktion (Young 1999, Buhl et al 2005, Young et al 2005, Sleeper et al 2014. Pferde zeigen dabei ähnli-che trainingsinduzierte Anpassungen des Herzens wie der Mensch, wobei diese Anpassungen beim Pferd jedoch meistens etwas geringer ausgeprägt sind (Harmeyer 2005).…”
Section: Introductionunclassified